Eigenfunctions for smooth expanding circle maps - Keller, Gerhard; Rugh, Hans Henrik (Nonlinearity, 2004)
We construct a real-analytic circle map for which the corresponding Perron-Frobenius operator has a real-analytic eigenfunction with an eigenvalue outside the essential spectral radius when acting upon C1-functions.
UnivIS-Import:2015-03-09:Pub.2004.nat.dma.pma29.eigenf